Donor-recipient specificity and age-dependency in fecal microbiota therapy and probiotic resolution of gastrointestinal symptoms - Qinglong Wu; Prapaporn Boonma; Shyam Badu; Nazlı Yalçınkaya; Sik Yu So; Kevin W. Garey; Kent C. Williams; L. Eugene Arnold; Robert J. Shulman; Richárd Kellermayer; Tor Savidge (npj Biofilms and Microbiomes, 2023)
Fecal microbiota transplantation (FMT) has proven to be an effective treatment for recurrent Clostridioides difficile infection (rCDI) in both adult and pediatric patients. However, as microbiome development is a critical factor in children, it remains unclear whether adult fecal donors can provide age-appropriate functional restoration in pediatric patients. To address this issue, we conducted an integrated systems approach and found that concordant donor strain engraftment, along with metabolite restoration, are associated with FMT outcomes in both adult and pediatric rCDI patients. Although functional restoration after FMT is not strain-specific, specialized metabolic functions are retained in pediatric patients when adult fecal donors are used. Furthermore, we demonstrated broad utility of high-resolution variant-calling by linking probiotic-strain engraftment with improved gastrointestinal symptoms in adults with irritable bowel syndrome and in children with autism spectrum disorder. Our findings emphasize the importance of strain-level identification when assessing the efficacy of probiotics and microbiota-based therapeutics.
Keywords: Clostridium difficile and Clostridium perfringens research; Gut microbiota and health; Gastrointestinal motility and disorders